Child Sexual Abuse from a Neurocriminological Perspective: A Multidisciplinary Analysis - Konoras, Isyana Kurniasari (SPECTRUM: Journal of Gender and Children Studies, 2025)
Child sexual abuse (CSA) is a grave criminal offense that profoundly impacts the victims' psychological, physical, and social well-being. While conventional criminological approaches have focused on sociological and psychological determinants, neurocriminology offers a new dimension by exploring neurological and biological correlates of deviant behavior. This paper aims to analyze CSA through the lens of neurocriminology, particularly the neural dysfunctions and brain abnormalities frequently observed in perpetrators. Using a qualitative literature review, this study synthesizes findings from neuroimaging and neuroscientific research. Evidence suggests that abnormalities in the prefrontal cortex, amygdala, and limbic system are significantly correlated with impaired impulse control, emotional regulation, and deviant sexual behavior. These findings emphasize the need for interdisciplinary frameworks in addressing CSA—combining legal, neurological, and psychological strategies to enhance both prevention and rehabilitation. The paper concludes with recommendations for justice systems to consider neuroscientific insights when handling CSA cases.